PENATALAKSANAAN FISIOTERAPI PADA KASUS TRIGGER FINGER DEXTRA DENGAN MODALITAS ULTRASOUND, TERAPI LATIHAN DAN AUTO STRECHING - nouval ridani; Indah Permata Sari; Ririn Amisa (Jurnal Kajian Ilmiah Kesehatan dan Teknologi, 2022)
ABSTRA ABSTRACT Background: Trigger finger is a disease that occurs in the fingers, caused by inflammation and narrowing of the sheath tendon around the tendon and the presence of a lump like nodules formed on the tendon causing pain in the fingers in addition to signs symptoms of trigger finger such as pain, limited range of joint motion. This study aims to determine the effect of physiotherapy intervention on the condition of the trigger finger sinistra. This type of this study is a case study. This study is done to one patient with the intervention ulra sound, auto stretching and exercise therapy.To find out the benefits of Ultrasound exercise therapy and auto stretching. After doing therapy 6 times with ultrasound, exercise therapy, auto stretching. In get the results of a decrease in pain, An increase in muscle strength, and an increase in joint range of motion. It is recommended for patients to routinely carry out therapy so that the optimal healing and repair process can be achieved. After doing 6 times therapy with ultrasound modalities, exercise therapy, auto stretching. in get the results of a decrease in pain, an increase in muscle strength, and an increase in joint range of motion.